Anti-Trypanosoma cruzi Properties of Sesquiterpene Lactones Isolated from Stevia spp.: In Vitro and In Silico Studies - Borgo, Jimena (2023)
Stevia species (Asteraceae) have been a rich source of terpenoid compounds, mainly sesquiterpene lactones, several of which show antiprotozoal activity. In the search for new trypanocidal compounds, S. satureiifolia var. satureiifolia and S. alpina were studied. Two sesquiterpene lactones, santhemoidin C and 2-oxo-8-deoxyligustrin, respectively, were isolated. These compounds were assessed in vitro against Trypanosoma cruzi stages, showing IC50 values of 11.80 and 4.98 on epimastigotes, 56.08 and 26.19 on trypomastigotes and 4.88 and 20.20 µM on amastigotes, respectively. Cytotoxicity was evaluated on Vero cells by the MTT assay. The effect of the compounds on trypanothyone reductase (TcTR), Trans-sialidase (TcTS) and the prolyl oligopeptidase of 80 kDa (Tc80) as potential molecular targets of T. cruzi was investigated. Santhemoidin C inhibited oligopeptidase activity when tested against recombinant Tc80 using a fluorometric assay, reaching an IC50 of 34.9 µM. Molecular docking was performed to study the interaction between santhemoidin C and the Tc80 protein, reaching high docking energy levels. Plasma membrane shedding and cytoplasmic vacuoles, resembling autophagosomes, were detected by transmission microscopy in parasites treated with santhemoidin C. Based on these results, santhemoidin C represents a promising candidate for further studies in the search for new molecules for the development of trypanocidal drugs.